DESIGN OF NATURAL FIBER POWDER MACHINE - Latief, Alfan Ekajati; Ali, Ali; Nassem, Zidane; Ramadan, Riski Gunarto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Natural fiber processing is the type of fiber as raw materials for textile or other industries that can be obtained directly from nature. In the Indonesian automotive industry, the manufacture of parts in vehicles is Polypropylene high impact (PPHI). An example of an existing part is a CVT slide piece made with a mixed polymer composite material from PPHI and pineapple leaf fiber. Pineapple leaf fibers with small sizes are needed so that the mixing of polymer composites is good. Therefore modern technology is required to process pineapple leaf fibers. This final project makes a natural fiber powder machine for processing natural fiber, namely scavenging. The research methodology used is a prescriptive design method. The design results produce a natural fiber powder machine (pineapple leaf fiber) for polymer composite materials with long size specifications of 420 mm long, 300 mm wide, and 582 mm high. The production capacity of the natural fiber storage machine is 5 kg/h. The source of the engine drive is a 1 HP AC electric motor with a rev of 2800 rpm. The transmission system uses a V-belt with a drive shaft 30 mm in diameter. The frame construction is made of a 35x35x5 mm profile with ST42 material and knives using S45C material (AISI 1045) with a thickness of 10 mm. It uses nine dynamic blades and six sharp plane fixed blades in a 30-degree active blade and a 60-degree fixed blade.